Inovasi Strategi Keuangan RSUD Dr Adjidarmo Lebak dalam Peningkatan Pendapatan - Rd. Novi Firani Rahmarani; Endang Komara; Rizki Adriansyah Rubini; Erliany Syaodih (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2025)
In the midst of increasing operational cost pressures and demands for quality health services, the ability of regional hospitals to be financially independent is crucial. Financial strategy innovation includes various approaches, ranging from optimising BPJS Health claims management, diversifying medical services, developing strategic business units, to sustainable operational cost efficiency. This study aims to analyse the implementation and impact of financial strategy innovation in an effort to increase revenue at Dr Adjidarmo Lebak Regional General Hospital (RSUD). Using a descriptive qualitative method, it collected data through interviews with financial management, service unit leaders, and relevant staff, as well as analysis of internal hospital documents. The findings show that RSUD Dr Adjidarmo Lebak has implemented several financial strategy innovations, such as improving the accuracy of coding and claims verification, introducing cashless services, and developing speciality services that are in demand by the community. Nonetheless, challenges such as limited trained human resources and fluctuations in health policies remain obstacles. The implications of this study emphasise the importance of adaptive leadership and organisational commitment to continuously innovate in financial management for financial sustainability and improved service quality of the RSUD.